2001
DOI: 10.1002/1521-3951(200103)224:1<253::aid-pssb253>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

PbS(Se) Quantum Dot Doped Glass Applications as Laser Passive Q‐Switches

Abstract: A. M. Malyarevich 1 ) (a), V. G. Savitsky (a) I. A. Denisov (a), P. V. Prokoshin (a), Subject classification: 78.66.Jg; 78.67.Hc; S8.11; S8.12; S10.15 Nonlinear optical properties of phosphate and silicate glasses doped with PbS and PbSe quantum dots of different sizes were studied. Absorption saturation intensity in the range of the first and second excitonic transitions was estimated. Passive Q-switch operation of glasses doped with PbSand PbSe-quantum dots as saturable absorbers for 1.067 mm Nd 3+ : KGd(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Furthermore, the wavelengths of PL from theses quantum dots are located in the near-infrared region that can be used to amplify the optical signals for the communications [4]. Lead-salt QDs also can be applied to the infrared lasers [5] and solar cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the wavelengths of PL from theses quantum dots are located in the near-infrared region that can be used to amplify the optical signals for the communications [4]. Lead-salt QDs also can be applied to the infrared lasers [5] and solar cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…This feature determines the possibility of using glasses with quantum dots as Q-switches and mode locking elements, including mode locking devices for Kerr-lens mode-locked solid-state lasers. At present, glasses with quantum dots have already been used for generating short pulses by the lasers operating in the spectral ranges 0.7-0.9, 1.06-1.08, and 1.2-1.3 µ m [1][2][3]. However, glasses with quantum dots have not been used in the longer wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable interest in these objects is caused by their possible application in infrared optoelectronics in the spectral range 1-3 µ m. Recent investigations [1][2][3] have demonstrated that silicate glasses doped with quantum dots can be used as saturable absorbers for passive mode locking in solid-state lasers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these and other properties of glasses can be essentially modified if they are embedded with nanoscale crystalline inclusions. Depending on the inclusion composition and structure, such glassy materials behave similarly to crystalline ones and demonstrate effective saturable absorption [3] and optical limiting [4], high electrooptical [5] and optical [6] Kerr sensitivities, second harmonic generation [7,8], and enhanced rare-earth ion luminescence [9]. If these materials are transparent and allow formation of optical waveguides, they could be used to develop new types of integrated optics structures.…”
mentioning
confidence: 99%